(untitled) (Nueva Epoca, 2020)
As the Article 281 from the Nation ́s Civil and Commercial Code ( CCCN ) states, the expression of the end goal (2) , is a valuable tool for conflicts preven- tion in family partnerships. Five years have passed since the CCCN entered into force and the expression of the end goal remains as an unexplored subject. The expression of the end goal in statutes or social agreements, represents another expression of the existing willingness’ autonomy even when the Gene- ral Law of Partnerships seems strict. The inclusion of the end goal, as well as the different clauses linked to willingness ‘autonomy, are simply incorporated into the SAS , which are regulated by the Entrepreneurial Capital Support Law ( LACE ), since its structure exhibits this willingness’ autonomy as a mainstay.